Method for manufacturing dielectric film with mixed slurry layer of PI for solid and solid-state-like batteries
By introducing a polyimide modifier into the LLZO mixed slurry layer to form a dielectric film, the problem of LLZO's easy reaction with air and water in solid-state batteries is solved, improving the stability of the electrolyte and the performance of lithium batteries, making it particularly suitable for electric vehicles and aerospace.
Patent Information
- Application Number
- CN202411285712.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2026-03-20
AI Technical Summary
In solid-state batteries, LLZO readily reacts with air and water to form an unstable interface layer, resulting in poor electrolyte performance and stability, and affecting the conduction of lithium ions.
Introducing a polyimide (PI) modifier into the LLZO mixed slurry layer, and combining it with PVDF, LiTFSI and LLZO particles to form a dielectric film, reduces the surface energy of LLZO and improves its surface stability and thermochemical stability.
It enhances the surface stability of the solid electrolyte, improves the ionic conductivity and thermal stability of LLZO, and extends the lifespan of solid lithium batteries, making it suitable for applications requiring high safety and stability.
Smart Images

Figure CN121709849A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to dielectric films for solid and solid-like electrolytes, and more particularly to a method for manufacturing a dielectric film having a PI mixed slurry layer for solid and solid-like batteries. Background Technology
[0002] Traditionally, solid-state or solid-state batteries typically include a positive electrode, a negative electrode, and a dielectric film located between the positive and negative electrodes. The dielectric film, situated between the positive and negative electrodes, serves to isolate the electrodes and allow lithium ions to pass through. The dielectric film generally comprises a PE (Polyethylene) layer 101 or other dielectric material layer with a thickness between 5 and 10 micrometers.
[0003] In practical applications, the dielectric film has at least one mixed slurry layer and an alumina layer on each side, with the alumina layer primarily serving to form a supporting structure. The mixed slurry layer includes LLZO, a solid electrolyte material with high ionic conductivity, good thermal stability, and chemical resistance, making it an ideal candidate material for next-generation solid-state lithium batteries. However, LLZO has a high surface energy and readily reacts with media such as air and water, generating unstable interface layers that reduce the performance and stability of the solid electrolyte.
[0004] However, the traditional application of LLZO as an ion-conducting mixed slurry layer suffers from excessively high band density and poor stability, resulting in inadequate overall lithium-ion conductivity. Based on the inventors' extensive knowledge in the chemical industry, polyimide (PI) modifiers are polymer materials with excellent heat resistance, chemical resistance, and electrical insulation. Introducing polyimide (PI) modifiers into LLZO can effectively reduce its surface energy and improve its surface stability. Therefore, the inventors sought a novel technology to effectively incorporate polyimide (PI) modifiers into the mixed slurry layer, thereby improving the overall properties of the mixed slurry layer.
[0005] The synthesis of this polyimide (PI) modifier is briefly described as follows: Fluorinated anhydride monomers, such as 6-FDA (hexafluorodianhydride), and other suitable diamine monomers are first dissolved separately in GBL (gamma-butyrolactone) solvent, and then slowly injected into a reaction vessel. The reaction vessel temperature is heated to 220℃, and an appropriate amount of catalyst is added and stirred for 5 hours. After cooling, an appropriate amount of GBL solvent is added for dilution to obtain PI. PI exhibits good temperature resistance, with a Tg (glass transition temperature) exceeding 300℃. Summary of the Invention
[0006] Therefore, the purpose of this invention is to solve the aforementioned problems in the prior art. This invention proposes a method for manufacturing a dielectric film with a polyimide (PI) mixed slurry layer for solid-state and solid-like batteries. A polyimide (PI) modifier is added to this mixed slurry layer, enhancing the surface stability of the overall solid electrolyte of the battery. This effectively prevents the formation of an unstable interface layer due to the reaction of LLZO with media such as air and water, thus reducing the performance and stability of the solid electrolyte. Overall, this improves the interface stability of LLZO, enhances its ionic conductivity, thermal stability, and chemical resistance, and improves the performance and lifespan of solid-state lithium batteries. The dielectric film of this invention can be widely used in solid-state lithium batteries, especially suitable for applications requiring high safety and stability, such as electric vehicles, energy storage systems, and aerospace. The dielectric film prepared using the method of this invention can significantly improve the overall performance and lifespan of solid-state lithium batteries, possessing significant technical value and market potential.
[0007] To achieve the above objectives, this invention proposes a dielectric film with a PI mixed slurry layer for solid-state and solid-like batteries. The solid-state battery includes: a positive electrode, a negative electrode, and a dielectric film located between the positive and negative electrodes. The dielectric film includes: a PE (Polyethylene) layer; at least one dielectric film coated on the side of the PE layer; the dielectric film is composed of PVDF (polyvinylidene difluoride), multiple LLZO (lithium-lanthanum-zirconium oxide) particles, a polyimide (PI) modifier, and LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethanesulfonyl)imide). The polyimide (PI) modifier is a polymer material with good heat resistance, chemical resistance, and electrical insulation. Mixing the polyimide (PI) modifier with the LLZO particles can effectively reduce the surface energy of the LLZO particles and improve their surface stability. In the dielectric film, the weight ratio of the PVDF, the polyimide (PI) modifier, the plurality of LLZO particles, and the LiTFSI is 6~10:0.8~1.6:4~8:4~8.
[0008] This application also includes a method for manufacturing a dielectric film with a PI mixed slurry layer, wherein the solid-state battery includes: a positive electrode, a negative electrode, and a dielectric film located between the positive electrode and the negative electrode; wherein the dielectric film includes: a PE (Polyethylene) layer; at least one dielectric film coated on the side of the PE layer; the dielectric film is composed of PVDF (polyvinylidene difluoride), a plurality of LLZO (lithium-lanthanum-zirconium oxide) particles, a polyimide (PI) modifier, and LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethanesulfonyl)imide); the manufacturing steps of the dielectric film include: Step A: taking a plurality of LLZO (lithium-lanthanum-zirconium oxide) particles and a solvent, and mixing the two using a first mixer to form a first slurry; wherein the solvent is selected from GBL (gamma-Butyrolactone), DMAC (Dimethylacetamide), or NMP. (Methylpyrrolidone, N-methylpyrrolidone); Step B: Take PVDF (polyvinylidene difluoride), polyimide (PI) modifier, AIBN (azobisisobutyronitrile), and LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethanesulfonyl)imide); Mix the above four compounds using a second mixer to form a second slurry; Step C: Add the second slurry to the first slurry in a certain proportion to form a viscous mixed slurry; and Step D: Apply the viscous mixed slurry to one side of the PE layer using a coating machine. The mixed slurry layer is formed, and the PE layer coated with the mixed slurry layer is placed in an oven for baking to remove the liquid in the mixed slurry layer; at this time, the mixed slurry layer becomes a solid dielectric film coated on the PE layer, forming a dielectric film with a two-layer structure; the polyimide (PI) modifier is a polymer material with good heat resistance, chemical resistance and electrical insulation; mixing the polyimide (PI) modifier with the LLZO particles can effectively reduce the surface energy of the LLZO particles and improve the surface stability of the LLZO particles. After baking in step D, the mixed slurry layer only contains the PVDF, the multiple LLZO particles, the polyimide (PI) modifier and the dielectric film formed by LiTFSI.
[0009] The features and advantages of the invention will be further understood from the following description, and please refer to the accompanying drawings while reading. Attached Figure Description
[0010] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0011] Figure 1 This application displays a manufacturing process flowchart; Figure 2 This application shows a schematic diagram of step A of the operation; Figure 3 This application shows schematic diagrams of steps B and C. Figure 4 This diagram shows the structure of the dielectric film of this application, wherein the dielectric film has a two-layer structure; Figure 5 This application shows a schematic diagram of step D of the operation. Figure 6 This diagram shows the structure of the dielectric film of this application, wherein the dielectric film has a three-layer structure; Figure 7 This diagram shows the structure of the dielectric film of this application, wherein the dielectric film includes an aluminum oxide layer; Figure 8 This shows a structural diagram of the solid-state battery of this application. Detailed Implementation
[0012] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art can make similar extensions without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0013] The following is a detailed description of a preferred embodiment of the present application, in conjunction with the accompanying drawings, regarding its structural composition, effects, and advantages.
[0014] Please refer to Figures 1 to 8 The diagram illustrates a method for manufacturing a dielectric thin film with a PI-based mixed slurry layer for solid-state and solid-like batteries according to the present invention, comprising the following components: like Figure 8As shown, a typical solid-state battery includes: a positive electrode 10, a negative electrode 20, and a dielectric film 100 located between the positive electrode 10 and the negative electrode 20. The positive electrode 10 includes: a positive electrode substrate 11, a carrier material for supporting the positive electrode 10; a positive electrode slurry layer 12 coated on the positive electrode substrate 11, wherein the positive electrode slurry layer 12 includes: a positive electrode slurry 14 containing a binder; the positive electrode slurry 14 also includes a plurality of positive electrode particles 15, such as LCO (lithium cobalt oxide), NCM (lithium nickel cobalt manganese oxide), etc. The negative electrode 20 includes: a negative electrode substrate 21, a carrier material for supporting the negative electrode 20; a negative electrode slurry layer 22 coated on the negative electrode substrate 21, wherein the negative electrode slurry layer 22 includes: a negative electrode slurry 24 containing a binder; the negative electrode slurry 24 also includes a plurality of negative electrode particles 25, such as silicon carbide particles. The dielectric film 100 is located between the positive electrode 10 and the negative electrode 20, and is used to isolate the positive and negative electrodes and conduct lithium ions.
[0015] like Figure 6 As shown, the dielectric film 100 essentially comprises a PE (Polyethylene) layer 101 with a thickness between 5 micrometers and 10 micrometers. At least one dielectric film 55' is coated on the side of the PE layer 101. The overall thickness of each dielectric film 55' is between 1 micrometer and 6 micrometers. The total thickness of the dielectric film 100 does not exceed 20 micrometers.
[0016] like Figure 7 As shown, at least one aluminum oxide layer 103 may also be coated on the side of the PE layer 101. The aluminum oxide layer 103 mainly serves as a support. The thickness of the aluminum oxide layer 103 is between 1 micrometer and 5 micrometers. The aluminum oxide layer 103 is not suitable for the outermost side of the dielectric film 100.
[0017] The dielectric film 55' is composed of PVDF (polyvinylidene difluoride) 40, multiple LLZO (lithium-lanthanum-zirconium oxide) particles 30, polyimide (PI) modifier 42, and LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethanesulfonyl)imide) 46.
[0018] In the dielectric film 55', the weight ratio of the PVDF 40, the polyimide (PI) modifier 42, the plurality of LLZO particles 30, and the LiTFSI 46 is 6~10:0.8~1.6:4~8:4~8.
[0019] The dielectric film 100 has the following functions: improving mechanical strength to withstand the pressure during battery assembly, preventing dendrite growth and puncture, avoiding battery short circuits, improving ionic conductivity to meet the needs of high-power applications, and possessing excellent thermal and chemical stability, making it suitable for a wider operating temperature range and a longer service life.
[0020] In the aforementioned mixed slurry 50, the PVDF 40 can be used as an adhesive and also provides support properties to the dielectric film 100.
[0021] The polyimide modifier 42 is a polymer material with good heat resistance, chemical resistance, and electrical insulation. Mixing the polyimide modifier 42 with the LLZO particles 30 can effectively reduce the surface energy of the LLZO particles 30 and improve their surface stability.
[0022] The LLZO particles 30 are a solid electrolyte material with high ionic conductivity, good thermal stability and chemical resistance, and can be used as a lithium-ion conductor.
[0023] LiTFSI 46 is a lithium salt material that dissociates into lithium ions in a solvent, thereby increasing the conductivity of lithium ions. It can also be used to adjust the pH in the manufacturing process.
[0024] like Figures 1 to 5 The method for manufacturing the dielectric film 100 is as follows: Step A: Multiple LLZO (lithium-lanthanum-zirconium-oxide) particles 30 and solvent 32 are taken and mixed using a first mixer 200 to form a first slurry 35. The total weight percentage of the multiple LLZO particles 30 in the first slurry 35 is between 20wt% and 40wt%. The first mixer 200 is selected from a ball mill or an ultrasonic mixer.
[0025] The solvent 32 is selected from GBL (gamma-Butyrolactone), DMAC (Dimethylacetamide), or NMP (Methylpyrrolidone), with DMAC being preferred. The solvent 32 primarily serves to disperse and support the plurality of LLZO particles 30 and the compounds added later.
[0026] The mixing time is approximately 30 minutes to 1 hour. After mixing, the particle size of each LLZO particle 30 is between 100 nanometers and 5 micrometers.
[0027] Step B: Take PVDF (polyvinylidene difluoride) 40, polyimide (PI) modifier 42, AIBN (azobisisobutyronitrile) 44, and LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethanesulfonyl)imide) 46; mix the above four compounds 40, 42, 44, and 46 using a second mixer 220 to form a second slurry 45. This second mixer 220 can be a high-speed mechanical stirring device.
[0028] The PVDF 40 accounts for 30 wt% to 50 wt% of the weight of the second slurry 45; the total weight of the polyimide (PI) modifier 42 accounts for 4 wt% to 8 wt% of the weight of the second slurry 45; the total weight of the AIBN 44 accounts for approximately 1 wt% to 2 wt% of the weight of the second slurry 45; and the LiTFSI 46 accounts for 20 wt% to 40 wt% of the weight of the second slurry 45.
[0029] The PVDF 40 of this application can be used as an adhesive and can also provide support properties to the dielectric film 100.
[0030] The purpose of adding the polyimide (PI) modifier 42 is that polyimide is a polymer material with good heat resistance, chemical resistance and electrical insulation. Mixing the polyimide (PI) modifier 42 with the LLZO particles 30 can effectively reduce the surface energy of the LLZO particles 30 and improve the surface stability of the LLZO particles 30.
[0031] The primary function of adding AIBN 44 is to initiate a chelate reaction, thereby forming a cross-linked structure and enhancing the mechanical strength, chemical stability, and ionic conductivity of the electrolyte membrane. This is highly beneficial for improving the overall performance of the dielectric film in lithium-ion batteries.
[0032] LiTFSI 46 is a lithium salt material that dissociates into lithium ions in a solvent, thereby increasing the conductivity of lithium ions. It can also be used to adjust the pH in the manufacturing process.
[0033] Step C: The second slurry 45 is added to the first slurry 35 in a certain proportion to form a viscous mixed slurry 50. After mixing, the viscosity of the mixed slurry 50 is between 1500 and 5000 cps (centi-poise). After mixing, the content (solid content) of the components formed by the PVDF 40, the plurality of LLZO particles 30, the polyimide (PI) modifier 42 and the LiTFSI 46 in the entire mixed slurry 50 is 15wt% to 28wt%.
[0034] After mixing the first slurry 35 and the second slurry 45, the final mixed slurry 50 contains PVDF 40 at a weight percentage between 6 wt% and 10 wt%; polyimide (PI) modifier 42 at a weight percentage between 0.8 wt% and 1.6 wt%; the total weight of the plurality of LLZO particles 30 at a weight percentage between 4 wt% and 8 wt%; the total weight of LiTFSI 46 at a weight percentage between 4 wt% and 8 wt%; and the remainder being solvent 32 and AIBN 44. In the drying step described later, solvent 32 and AIBN 44 will evaporate or volatilize, leaving only the remaining substances.
[0035] Step D: The viscous slurry 50 is coated onto one side of the PE layer 101 using a coating machine 300 to form a slurry layer 55. The PE layer 101 coated with the slurry layer 55 is then placed in an oven 400 for baking to remove the liquid from the slurry layer 55. Before baking, the thickness of the slurry layer 55 is less than 25 micrometers. After baking, only the PVDF 40, the multiple LLZO particles 30, the polyimide (PI) modifier 42, and the LiTFSI 46 remain in the slurry 50; the remaining substances evaporate during baking. At this point, the slurry layer 55 becomes a solid dielectric film 55' coated onto the PE layer 101, forming a two-layer dielectric film 100 (e.g., ...). Figure 4 After baking, the dielectric film 55' becomes solid with an overall thickness between 1 micrometer and 6 micrometers.
[0036] The coating speed of the coating machine 300 is 5~10 m / min; the temperature of the oven 400 is 80°C~120°C, and the baking time is between 30 minutes and 1 hour.
[0037] like Figure 6As shown, a second layer of the mixed slurry layer 55 can be coated on either side of the PE layer 101 as needed, meaning the PE layer 101 has two layers of the mixed slurry layer 55. Then, the same baking process is repeated to form a three-layer dielectric film 100, with any number of dielectric film sheets 55' stacked as needed. The total thickness of the dielectric film 100 does not exceed 20 micrometers.
[0038] like Figure 7 As shown, the dielectric film 100 of the required number of layers can be formed by coating and baking the PE layer 101 as needed. In the above process, an aluminum oxide layer 103 can also be coated onto the PE layer 101 or the superimposed dielectric film 55' as needed. The aluminum oxide layer 103 mainly serves as a support. The thickness of the aluminum oxide layer 103 is between 1 micrometer and 5 micrometers, and the total thickness of the dielectric film 100 does not exceed 20 micrometers. The aluminum oxide layer 103 is not suitable for the outermost layer of the dielectric film 100.
[0039] The advantage of this application is that by adding a polyimide (PI) modifier, the solid electrolyte of the overall battery exhibits enhanced surface stability. This effectively prevents LLZO from reacting with media such as air and water to form an unstable interfacial layer, thus reducing the performance and stability of the solid electrolyte. Overall, it improves the interfacial stability, ionic conductivity, thermal stability, and chemical resistance of LLZO, and enhances the performance and lifespan of the solid-state lithium battery. The dielectric film of this invention can be widely used in solid-state lithium batteries, and is particularly suitable for applications requiring high safety and stability, such as electric vehicles, energy storage systems, and aerospace. The dielectric film prepared using the method of this invention can significantly improve the overall performance and lifespan of solid-state lithium batteries, possessing significant technical value and market potential.
[0040] In conclusion, the applicant's thoughtful and user-friendly design is highly in line with actual needs. Its specific improvements over existing deficiencies represent a significant breakthrough compared to existing technologies, offering genuine functional enhancements that are not easily achieved. This application has not been published or disclosed in domestic or foreign literature or markets, thus complying with patent law requirements.
[0041] The foregoing detailed description pertains to a feasible embodiment of the present invention, but this embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the spirit of the present invention should be included in the patent scope of this application.
Claims
1. A method for manufacturing a dielectric thin film with a PI hybrid slurry layer for solid-state and solid-like batteries, characterized in that, The solid-state battery includes: a positive electrode, a negative electrode, and a dielectric film located between the positive electrode and the negative electrode; The dielectric film includes: a PE layer; at least one dielectric film sheet coated on the side of the PE layer; the dielectric film sheet is composed of PVDF, multiple LLZO particles, polyimide modifier and LiTFSI; The method for manufacturing this dielectric film includes: Step A: Take multiple LLZO (lithium-lanthanum-zirconium-oxide) particles and solvent, and mix them together using a first mixer to form a first slurry; wherein the solvent is selected from GBL, DMAC or NMP; Step B: Take PVDF, polyimide modifier, AIBN, and LiTFSI; mix the above four compounds using a second mixer to form a second slurry; Step C: Add the second slurry to the first slurry in a certain proportion and mix to form a viscous mixed slurry; and Step D: Apply the viscous mixed slurry to one side of the PE layer using a coating machine to form the mixed slurry layer, and place the PE layer coated with the mixed slurry layer into an oven for baking to remove the liquid in the mixed slurry layer; at this time, the mixed slurry layer will become a solid dielectric film coated on the PE layer, forming a dielectric film with a two-layer structure.
2. The method according to claim 1, characterized in that, After mixing in step C, the viscosity of the mixed slurry is between 1500 and 5000 cps, and after mixing, the solid content of the component formed by the PVDF, the multiple LLZO particles, the polyimide modifier and the LiTFSI in the mixed slurry is between 15 wt% and 28 wt%.
3. The method according to claim 1, characterized in that, After baking in step D, the mixed slurry layer is left with only the PVDF, the multiple LLZO particles, the polyimide modifier, and the dielectric film formed by the LiTFSI.
4. The method according to claim 1, characterized in that, After mixing in step A, the particle size of each LLZO particle is between 100 nanometers and 5 micrometers, and after baking in step D, the overall thickness of the dielectric film becomes between 1 micrometer and 6 micrometers.
5. The method according to claim 1, characterized in that, In step A, the total weight of the plurality of LLZO particles accounts for a weight percentage of the first slurry between 20wt% and 40wt%.
6. The method according to claim 1, characterized in that, In step B, the PVDF accounts for a weight percentage of 30wt% to 50wt% of the second slurry; the total weight of the polyimide modifier accounts for a weight percentage of 4wt% to 8wt% of the second slurry; the total weight of the AIBN accounts for approximately 1wt% to 2wt% of the second slurry; and the LiTFSI accounts for a weight percentage of 20wt% to 40wt% of the second slurry.
7. The method according to claim 1, wherein in the mixed slurry, the PVDF is used as an adhesive and can also provide support properties for the dielectric film; the LLZO particles are used as lithium ion conductors; and the LiTFSI is a lithium salt material that increases the conductivity of lithium ions and can also be used to adjust the pH in the manufacturing process.
8. The method according to claim 6, characterized in that, In step C, after mixing the first slurry and the second slurry, the PVDF accounts for a weight percentage of 6wt% to 10wt% of the mixed slurry; the polyimide modifier accounts for a weight percentage of 0.8wt% to 1.6wt% of the mixed slurry; the total weight of the plurality of LLZO particles accounts for a weight percentage of 4wt% to 8wt% of the mixed slurry; the total weight of LiTFSI accounts for a weight percentage of 4wt% to 8wt% of the mixed slurry; and the remainder is the solvent and the AIBN.
9. The method according to claim 1, characterized in that, In step D, the coating speed of the coating machine is 5~10m / min; the temperature of the oven is 80°C~120°C, and the baking time is between 30 minutes and 1 hour.
10. The method according to claim 1, characterized in that, Depending on the requirements, another layer of the mixed slurry is applied to either side of the PE layer, and then the same baking steps are repeated to form a multi-layered dielectric film. Any number of dielectric film layers can be stacked as needed; wherein the total thickness of the dielectric film does not exceed 20 micrometers.
11. The method according to claim 1, characterized in that, Depending on the requirements, an aluminum oxide layer is then coated on either side of the PE layer; this aluminum oxide layer mainly serves as a support; the thickness of the aluminum oxide layer is between 1 micrometer and 5 micrometers, and the total thickness of the dielectric film does not exceed 20 micrometers.
